Study of nanosuspension droplets free evaporation and electrowetting - Orejon, Daniel (The University of Edinburgh, 2013)
Evaporation and wetting of droplets are a phenomena present in everyday life and in many industrial, biological or medical applications; thus controlling and understanding the underlying mechanisms governing this phenomena becomes of paramount importance. More recently, breakthroughs in the fabrication of new materials and nanomaterials have led to the synthesis of novel nanoscale particulates that dispersed into a base fluid modify the properties of this latter. Enhancement in heat transfer or the self-assembly of the particles in suspension during evaporation, are some of the areas in which nanofluids excel. Since it is a relatively new area of study, the interplay particle-particle, particle-fluid or particle-substrate at the macro-, micro-, and nanoscale is yet poorly understood. This work is an essay to elucidate the fundamental physics and mechanisms of these fluids during free evaporation, of great importance for the manipulation and precise control of the deposits. The evaporative behaviour of pure fluids on substrates varying in hydrophobicity has been studied and an unbalance Young’s force is proposed to explain the effect of substrate hydrophilicity on the pinning and the depinning forces involved during droplet evaporation. On other hand, the addition of nanoparticles to a base fluid modifies the evaporative behaviour of the latter and: a more marked “stick-slip” behaviour is observed when increasing concentration on hydrophobic substrates, besides the longer pinning of the contact line reported on hydrophilic ones when adding nanoparticles. A deposition theory to explain the final deposits observed, for the outermost ring, after the complete vanishing of a 0.1% TiO2-ethanol nanofluid droplet has also been developed. In addition, the evaporation of pinned nanofluid droplets on rough substrates at reduced pressures has been systematically studied. A revisited Young-Lippmann equation is proposed as one of the main findings to explain the enhancement on electrowetting performance of nanoparticle laden fluid droplets when compared to the pure fluid case. On the other hand, of relevant importance is the absence of “stick-slip” behaviour and the more homogeneous deposits found after the complete evaporation of a nanofluid droplet under an external electric field applied when compared to free evaporation of these fluids.
Keywords: droplet evaporation; nanofluids; patterning; electrowetting; interfacial phenomena